2021
DOI: 10.1186/s12902-021-00751-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic and lipid variability for predicting complications and mortality in diabetes mellitus using machine learning

Abstract: Introduction Recent studies have reported that HbA1c and lipid variability is useful for risk stratification in diabetes mellitus. The present study evaluated the predictive value of the baseline, subsequent mean of at least three measurements and variability of HbA1c and lipids for adverse outcomes. Methods This retrospective cohort study consists of type 1 and type 2 diabetic patients who were prescribed insulin at outpatient clinics of Hong Kong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 82 publications
3
44
0
Order By: Relevance
“…Diabetes is a well-recognized risk factor for the development of AF (Xiong et al, 2018), adverse cardiovascular events (Lee et al, 2021a;Lee et al, 2021b), complications involving different organs (Lee et al, 2020), and mortality. Of the different classes of antidiabetic drugs, thiazolidinediones act by activating PPAR-γ (Lebovitz, 2019;Veettil et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a well-recognized risk factor for the development of AF (Xiong et al, 2018), adverse cardiovascular events (Lee et al, 2021a;Lee et al, 2021b), complications involving different organs (Lee et al, 2020), and mortality. Of the different classes of antidiabetic drugs, thiazolidinediones act by activating PPAR-γ (Lebovitz, 2019;Veettil et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Both measures have been associated with a higher risk of complications and mortality in patients with diabetes mellitus in both randomized controlled trials and real-world settings. [51][52][53][54][55] There are several methods that can be used to calculate variability, such as SD, CV and score based on the frequency exceeding a fixed percentage change in the absolute values. Prior studies have demonstrated the Cardiovascular and metabolic risk importance of such measures of variability in the prediction of adverse outcomes, 16 17 but a systematic and direct comparison of different methodologies has not been made with regard to their predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with T2DM are more likely to be overweight or obese, which indicates insulin resistance and dyslipidemia along with hyperglycemia [ 5 , 6 ]. For T2DM patients, glycemic or lipid values and their variability can significantly predict all-cause mortality and the occurrence of complications, including micro- and macrovascular complications [ 7 , 8 ]. Growing evidence has indicated that chronic inflammation, hyperglycemia, and dyslipidemia are all involved in insulin resistance, pathogenesis of T2DM, and systematic diabetic complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%